Public Health in Developing Countries - Challenges and Opportunities 2020
DOI: 10.5772/intechopen.91859
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion and Its Challenges to Public Health Delivery System in Africa

Abstract: The chapter examines the place and role of health promotion in the drive for sustainable and effective public health delivery in Africa. It conceptualizes health promotion from a multifaceted and multi-professional perspective hinged on the empowerment of communities and individuals to play active roles and adopt behaviour consistent with the goals of good health. The paper drawing on documentary data sees health promotion as critical to the achievement of health goals in the continent and equally reflects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In Africa, health promotion policies have consistently prioritized the well-being of the population, even in the face of corruption and limited financial resources on the continent. Despite financial constraints, significant progress has been achieved in critical areas such as combating HIV/AIDS, controlling TB, addressing female genital mutilation, combating gender-based violence, promoting breastfeeding, and reducing maternal and under-5 mortality rates [76][77][78] However, studies have reported several deficiencies in the health promotion workforce structure, policies, as well as managerial supervision and monitoring. [79]…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, health promotion policies have consistently prioritized the well-being of the population, even in the face of corruption and limited financial resources on the continent. Despite financial constraints, significant progress has been achieved in critical areas such as combating HIV/AIDS, controlling TB, addressing female genital mutilation, combating gender-based violence, promoting breastfeeding, and reducing maternal and under-5 mortality rates [76][77][78] However, studies have reported several deficiencies in the health promotion workforce structure, policies, as well as managerial supervision and monitoring. [79]…”
Section: Discussionmentioning
confidence: 99%
“…Limited access to health promotion and disease prevention programs and healthcare services contribute to these health challenges. 17 This has an effect on low awareness of prenatal diagnosis for a variety of reasons, including long distances to hospitals, the economy, and employment. 16,18 Basically, prenatal diagnosis is done to detect 3 types of birth defects caused by structural defects, genetic syndromes, and chromosomal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The SCT considers both the personal and socio-structural aspects of health because a comprehensive approach to health promotion demands changing the practices of social systems that have pervasive determinantal effects on health rather than concentrating solely on changing the habits of individuals. 33 In the same vein, contemporary health promotion extends beyond recommending best practices. It encompasses initiatives to modify social and physical environments within communities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%